Cost-Utility Analysis of Drug Treatments in Patients with Polypoidal Choroidal Vasculopathy in Thailand - Sangroongruangsri S; Chaikledkaew U; Hanusaha P; Ratanapakorn T; Ruamviboonsuk P (Dove Medical Press, 2021)
Sermsiri Sangroongruangsri,1 Usa Chaikledkaew,1,2 Prut Hanusaha,3 Tanapat Ratanapakorn,4 Paisan Ruamviboonsuk5 1Social and Administrative Pharmacy Division, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 2Mahidol University Health Technology Assessment (MUHTA) Graduate Program, Mahidol University, Bangkok, Thailand; 3Department of Ophthalmology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 4Department of Ophthalmology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand; 5Department of Ophthalmology, Rajavithi Hospital, College of Medicine, Rangsit University, Bangkok, ThailandCorrespondence: Usa Chaikledkaew Tel +662-644-8679 ext 5317Fax +662-644-8694Email usa.chi@mahidol.ac.thPurpose: The aim of this study was to estimate the cost-utility and budget impact of pharmacological treatments for the eye with polypoidal choroidal vasculopathy (PCV) in Thailand.Methods: A Markov model-based cost-utility analysis (CUA) and budget impact analysis were conducted. The lifetime cost and outcomes of PCV treatments were estimated. We discounted costs and outcomes at 3% per annum. Parameters were estimated using data from published literatures, local cost and utility data, and epidemiology data among Thai patients. Univariate and probabilistic sensitivity analyses were performed to account for parameter uncertainty.Results: Intravitreal bevacizumab (IVB) resulted in the lowest lifetime cost, followed by IVB plus verteporfin photodynamic therapy (IVB+vPDT) and intravitreal aflibercept (IVA). The combination of IVB or intravitreal ranibizumab (IVR) and verteporfin photodynamic therapy (IVB+vPDT or IVR+vPDT) yielded the highest quality-adjusted life-years (QALY). When compared with IVB from a societal perspective, the incremental cost-effectiveness ratio for patients with PCV receiving IVB+vPDT, IVR+vPDT, IVA were 10,304; 54,135; and 82,738 the United States dollar (USD) per QALY gained, respectively. At the Thai societal willingness to pay threshold of 4884 USD, IVB had the highest probability of being cost-effective (99%) followed by IVB+vPDT (1%). IVB+vPDT could be a cost-effective strategy and required a budget of 12.61 million USD over five fiscal years when the price of verteporfin reduced by approximately 45%.Conclusion: None of the drug treatments for PCV was cost-effective in the Thai context. The decreased price of verteporfin is required to support the inclusion of IVB+vPDT in the Thai National List of Essential Medicines for the treatment of PCV.Keywords: PCV, verteporfin, anti-VEGF agent, retinal disease, economic evaluation, Thailand